THE EFFECT OF RICE WASHING WATER AND COCONUT WATER ON THE GROWTH OF TOMATO PLANT (Lycopersium esculentum Mill.) IN MANGGARAI REGENCY - Choirunnisa, Jessyca Putri; Putri, Maria Marselina Ade; Lau, Margareta Skolandia Lau Skolandia; Unggut, Yuliana Yurianti Sartika (MEDIAGRO, 2024)
Tomato are vegetable commodity with high economic value and widely consumed by Indonesian people. The increase in tomato consumption is not matched by an increase in production. Tomato production in Manggarai Regency has decreased due to excessive use of inorganic fertilizers. Providing organic materials with rice washing water and coconut water can reduce the use of inorganic fertilizers. This study aims to determine the effect of rice washing water and coconut water on tomato growth, and determining the appropriate concentration of rice washing water and coconut water to increase tomato growth. This study was conducted in September-November 2023 on the Food Security and Horticulture Demonstration Plot of Kodim 1612 Manggarai. This study used a non-factorial Randomized Block Design in the form of coconut water and rice washing water consisting concentrations with 4 levels (0 ml rice washing water + 0 ml coconut water; 250 ml rice washing water + 250 ml coconut water; 350 ml rice washing water + 150 ml coconut water; 450 ml rice washing water + 50 ml coconut water) and each treatment was four repeated. The study showed that the concentration of rice washing water and coconut water had a significant effect on plant height, number of leaves, leaf area and stem diameter in tomato plants, but had no significant effect on the number of branches. The concentration of 450 ml rice washing water + 50 ml coconut water can produce the tallest plant (155.24 cm) and the highest number of branches (11.65 branches), while a concentration of 250 ml rice washing water + 250 ml coconut water can produce the highest number of leaves (197.43 leaves), highest leaf area (36.23 cm2) and highest stem diameter (0.88 cm).